Late Pleistocene flora of the Kiryas-L site according to palynological and algological analysis (West Siberia, Russia) - A. T. Galimov; A. S. Shakhmatov (Проблемы ботаники Южной Сибири и Монголии, 2023)
The article provides results of palynological and algological analysis of peat deposits from MIS-5c in the Kiryas site. Sampling and analysis were carried out from the same horizon that was analyzed by other methods in already published works with the dating of the underlying layer at 105.5 ± 3.6 thousand years ago. Algological analysis and spore-pollen analysis were carried out. Three successive changes in vegetation were identified in the territories adjacent to the studied section. Changes in the composition of algal communities were used to trace changes in watering and the trophic status of the peat bog. Peat formation began with warming in time after 105 thousand years ago, with forest-tundra vegetation; in the second stage, a biome close to the modern northern taiga was formed; in the third stage, cooling occurred with the formation of a forest-tundra community and the end of peat formation. Complex conjugate analysis of stratigraphic records by various methods increases the reliability of reconstructions of natural changes. The abundance of algae remains allows us to conclude that the water level and the trophic status of the peat bog have changed.